The essential guide to effect sizes : statistical power, meta-analysis, and the interpretation of research results - Ellis, Paul D., 1969- (Cambridge ; New York : Cambridge University Press, 2010)
"This succinct and jargon-free introduction to effect sizes gives students and researchers the tools they need to interpret the practical significance of their results. Using a class-tested approach that includes numerous examples and step-by-step exercises, it introduces and explains three of the most important issues relating to the practical significance of research results: the reporting and interpretation of effect sizes (Part I), the analysis of statistical power (Part II), and the meta-analytic pooling of effect size estimates drawn from different studies (Part III). The book concludes with a handy list of recommendations for those actively engaged in or currently preparing research projects"--
Introduction to effect sizes -- Interpreting effects -- Power analysis and the detection of effects -- The painful lessons of power research -- Drawing conclusions using meta-analysis -- Minimizing bias in meta-analysis.
Includes bibliographical references (p. 153-169) and index.
Keywords: Research -- Statistical methods; Sampling (Statistics)